Study on The Effects of Boron on The Structure of Chloroplasts of Cauliflower , By Using Light Scattering Technique - Al-Qysi, H. M.A.; ALMola, R. M.M.; Alani, N. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Effects of Boron on the structure of chloroplasts membrane isolated from cauliflower are investigated , using light scattering technique. Results obtained in this study suggest that Boron in the concentration range (0.1-5 µm) can fluidize the lipids of the chloroplast membrane due to different extent. Mechanisms by which Boron can change the lipid fluidity is discussed. Furthermore, an experimental evidence is presented to show that2µM Boron can mediate conformational changes in the membrane –bound proteins of the cauliflower’s chloroplast.